Early prevention of radial artery occlusion via distal transradial access for primary percutaneous coronary intervention - Wang, Yujie; Liu, Zijing; Wu, Yongxia; Li, Zixuan; Wang, Yuntao; Wang, Senhu; Xu, Rong; Zhang, Libin; Wang, Yuping; Guo, Jincheng (Frontiers in Cardiovascular Medicine, 2022)
Background Conventional transradial access (TRA) has been the preferred access for coronary intervention. Recently, distal radial access (DRA) is introduced as an alternative choice to reduce radial artery occlusion (RAO) risk. The study sought to assess the impact of DRA on early RAO using Doppler ultrasound in patients with ST-segment elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (PCI). Methods This is a prospective, single-center, open-label randomized clinical trial in which patients with indications for primary PCI from January 2022 to September 2022 were assigned to DRA or TRA group with 100 cases in each group. The primary endpoint was the incidence of forearm RAO, evaluated by Doppler ultrasound before discharge. Results The rate of access success was comparable between the DRA and TRA groups (98.0 vs. 94.0%, P = 0.279). Compared with the TRA group, longer puncture time was observed in the DRA group [2.4 (1.7–4.2) min vs. 1.7 (1.4–2.3) min; P < 0.001] whereas the door-to-wire time was not delayed in primary PCI [71 (54–88) min vs. 64 (56–82) min, P = 0.103]. Shorter hemostasis time was required in the DRA group [3.1 (2.7–3.3) h vs. 6.2 (5.9–6.4) h; P < 0.001]. Significant reduction of the incidence of forearm RAO was observed in the DRA group (2.0 vs. 9.0%, P = 0.030). Local hematomas ≤ 5 cm was similar in both groups (4.0 vs. 6.0%, P = 0.516), while those > 5 cm were significantly more frequent in the TRA group (0 vs. 6.0%, P = 0.029). Conclusion Distal radial access is associated with a comparable lower incidence of forearm RAO, shorter hemostasis time, and lower rate of vascular complications compared to TRA in primary PCI. Systematic review registration [https://www.chictr.org.cn], identifier [ChiCTR2200061841].